Ulama, Islam, dan Gerakan Sosial-Politik: Reposisi Ulama dalam Gerakan Sosio-Politik Islam Indonesia - Dinul Husnan; Muhammad Sholihin (Institut Agama Islam Negeri (IAIN) Curup, 2017)
The ‘ulama, or Islamic Clergies are not only as an Islamic scholars who have Islamic science largely, but also an charismatic political leader for Indonesian Moslem. Historically, they have an important roles in Indonesia-war in fighting the colonialism—Dutch and Japan imperialism. Finally, they are struggle element in achieving indonesian freedom. The paper aims to highlight the relation between ‘ulama movement, especially Syekh Musthafa Hussein Nasution and islamic socio-politic movement in Indonesia. The library research is implemented as approach the study. To sum up, Syekh Musthafa Hussein Nasution is an ulama who have main figure behind Islamic Movement in North Sumatera. Generaly in Indonesia. He offer an unique movement like economic and education movement, simultaneously.